Contemporary Fiqh Methodology in the Theory of the Limitation of Dialectics Space and Time According to Muhammad Syahrur - Sakirman, Sakiman (Hunafa: Jurnal Studia Islamika, 2017)
The hudûd Syahrûr theory is designed to manifest fiqh apart from the dominance of the tyrannical system as it occurs in classical Islamic fiqh. This theory wants to realize the Islamic law that is formed in the corridor of the law (al-fiqh ad-dustur). According to Syahrûr, the need for al-fiqh ad-dustur is very urgent because the fiqh of Islam that has been so far is relying on the character (fuqaha) personally, not institutional. Therefore, the existence of a legal democracy or a judiciary free from executive influence is very difficult to find in Islamic legal thought. Because Islam is always associated with the figure then the Islamic judiciary, for example also always depends on the face of judges. If the judges are good, then the Islamic judiciary will look good, and so if otherwise, if the judges are ugly then the Islamic judiciary will also look bad. As is the case in the Middle East, in the context of the Islamic world, hudûd theory also arises in connection with Syahrûr's efforts to uphold democracy and civil liberties, especially in jurisdictions. This emergence was driven by Syahrûr's concern in looking at the decadence experienced by Islamic law in the modern world. Syahrûr assumes that in the field of law, the Islamic world is currently experiencing an acute crisis. Therefore, he considers that the existence of new fiqh formed based on new methods is very urgent to be realized. The hudûd theory is part of a new method proposed by Syahrûr in contemporary Islamic legal thought. Therefore, this paper examines aspects of contemporary methodology in hudud theory concept initiated by Muhammad Syahrur.